Development of the Koribantes Young Generation Dance for Millennials and Z Generation - Surya Adi Saputra; ME Winarno; Lokananta Hari Wiguno (INSPIREE: Indonesian Sport Innovation Review, 2022)
The purpose of the study. The goal to be achieved is to produce a new gymnastics, with the name "Koribantes Young Generation Dance" which is a new gymnastics that is different from the usual Physical Fitness as an innovation of gymnastics whose objects are young people with a touch of music and movements according to the soul. their youth form of modern dance gymnastics. Materials and methods. The research method used is a model development research method in which a process or steps to develop a new product based on the theory of Research & Development. Results. The results of this study produce a new gymnastics: (1) New gymnastics that is devoted to for the millennial generation and generation Z (2) the development of a cardio training model with dance (3) The results of the effectiveness test of this exercise are feasible to use. Conclusions. From the results of small group trials and large group trials as well as discussion of research results, it can be concluded that "Koribantes Young Generation Dance" deserves to be a gymnastic product used by millennials and generation Z as a form of cardio training program to train strength keep heart and lung.